Performance improvement model in a manufacturing company: job satisfaction as mediator - Dewi, Santi Riana; Gentari, Ratu Erlina; Kurnia, Denny; Deviyantoro, Deviyantoro (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
This study’s goal is to determine the effect of work placement and work discipline on performance with job satisfaction as an intervening variable among a manufacturing company during the COVID-19 pandemic. This study design is causal-comparative with a quantitative approach with 100 respondents. The study's findings indicated that work placement had a direct impact on performance, work discipline had a direct impact on performance, job satisfaction had a direct impact on performance, work discipline had a direct impact on job satisfaction, and work placement had a direct impact on job satisfaction. Work discipline did not significantly have an indirect effect on performance.